2014
DOI: 10.5301/ijao.5000373
|View full text |Cite
|
Sign up to set email alerts
|

Recirculation during Veno-Venous Extra-Corporeal Membrane Oxygenation – a Simulation Study

Abstract: therefore total dependency on the ECMO circuit. The optimal degree of lung rest may therefore depend not only on pulmonary pathophysiology, but also the center-specific risk of technical complications during ECMO treatment. Left ventricular and arterial oxygen saturation during VV-ECMO with collapsed lungs may approach the saturation in the pulmonary artery. This saturation is determined by the efficiency of VV-ECMO therapy, lung function, cardiac output, and oxygen consumption. The blood leaving the oxygenato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 20 publications
3
41
0
Order By: Relevance
“…In order to enhance bedside clinical decision support, we introduced a real-time, patient-specific simulation model of cardiovascular dynamics [ 6 , 7 ]. The model is built with 32 0-D compartments in total; four cardiac chambers, pericardium, intrathoracic space and 27 vascular compartments including systemic circulation, pulmonary circulation and coronary circulation.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In order to enhance bedside clinical decision support, we introduced a real-time, patient-specific simulation model of cardiovascular dynamics [ 6 , 7 ]. The model is built with 32 0-D compartments in total; four cardiac chambers, pericardium, intrathoracic space and 27 vascular compartments including systemic circulation, pulmonary circulation and coronary circulation.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…A previous study has shown that preoxygenator saturation ( S preox O 2 ) is an unreliable measure of treatment efficiency in VV‐ECMO . The venous saturations in the superior caval vein and inferior caval vein may differ as much as 25% or more in VA‐ECMO and S preox O 2 is dependent on the relative contribution from these two sources.…”
Section: Discussionmentioning
confidence: 99%
“…A closed‐loop real‐time simulation model was developed consisting of 27 vascular segments, the four cardiac chambers with corresponding valves, septal interactions, the pericardium and intrathoracic pressure (Fig. ) published elsewhere . The cardiac chambers are represented as time‐varying elastances and the closed‐loop vascular system segments characterized by nonlinear resistances, compliances, inertias and visco‐elastances.…”
Section: Patient and Methodsmentioning
confidence: 99%
“…Most centers prefer to drain desaturated venous blood via the inferior vena cava and return the saturated blood through the superior vena cava into the right atrium. With this approach, it is possible to achieve higher saturations due to reduced blood recirculation compared to the technique at the ECMO Department Karolinska [28,29]. However, from my clinical experiences, the limitation of the former approach is that the total extracorporeal flow, i.e., the level of oxygen delivery by ECMO that can be reached, is less with this method than with the method used at the ECMO Department Karolinska, particularly in the awake and dehydrated patient, as the venous drainage through the IVC is dependent on the hydration of the patient and the intraabdominal pressure.…”
Section: Techniquementioning
confidence: 99%